Study the Antimicrobial Resistance Genes of Listeria Monocytogenes Isolated From Industrial and Clinical Samples in Iraq - Al-Brefkani, Azad Mohammed Taher (Iraqi Journal of Science, 2023)
Multi-drug resistance in Listeria monocytogenes is considered a major public health problem associated with foodborne outbreaks and causes high hospitalization and mortality rates. This study aimed to investigate the antimicrobial resistant genes among Listeria monocytogenes isolated from meat and clinical samples. Phenotypically, the isolates were tested for their susceptibility against the 12 most commonly used antimicrobials in veterinary and human therapy via the disc diffusion method, while conventional PCR was performed to study the presence or absence of 14 resistance genes predicted in L. monocytogenes isolates. The study established that 30(66.66%) of L. monocytogenes isolates showed phenotypic multi-drug resistance against at least three antimicrobial classes. Furthermore, high resistance frequencies were reported among commonly used antibiotics for listeriosis therapy. The present study revealed that the investigated isolates show resistance against tetracycline 33(73.3%), ampicillin 29(64.4%), penicillin 28(62.2%), erythromycin 26(57.8%), and gentamycin, clindamycin and vancomycin 24(53.3% each). Of the 45 L. monocytogenes isolates studied, 37(82.2%) were phenotypically susceptible to meropenem, followed by ciprofloxacin 36(80.0%) and SXT 30(66.7%). PCR amplification of antimicrobial resistance genes established the occurrence of antibiotic resistance genes in all studied L. monocytogenes isolates. Notably, 41(91.11%) of these isolates exhibited more than five resistance genes. Surprisingly, penA and ampC were detected in all L. monocytogenes strains   45(100%), followed by ermB 44(97.8%), tetA 38(84.4%), tetG 32(71.1%), and vanB 30(66.7%). Moreover, vanA 22(48.9%) and tetB 18(40.0%) were detected less frequently. The lowest incidences of resistance genes were observed in L. monocytogenes carrying tetD 4(8.9%) and cmlA 6(13.3%). In conclusion, the study demonstrates that the majority of L. monocytogenes from human and meat samples displayed a high index of resistance to a variety of agents used for clinical listeriosis treatment adding further burden to the existing global antibiotic resistance problem.